Analysis of Dysfunctional Marriage Through Conflicts in Gillian Flynn's Gone Girl (2012) - Tyas, Nimas Arum Suryaning (Universitas Negeri Surabaya, 2022)
This study aims to analyze the dysfunctional marriage of Amy and Nick Dunne through the conflicts that occur in their marriage. Dysfunctional marriage is the breakdown of marital relations, and marriage does not run as healthy as it should. A marriage can become dysfunctional because of the insoluble conflict that surrounds the marriage. This study is a literary study that uses textual information in the novel as the basis for its analysis. The primary data in this study is the novel Gone Girl by Gillian Flynn, along with journal articles and other supporting information. The study was conducted by analyzing the conflict, which depicts that Nick and Amy's marriage is in a dysfunctional condition. The results showed several conflicts, such as lack of communication, dissatisfaction, and dishonesty, that occurred in Amy and Nick Dunne's marriage, which were based on themselves, which was why their marriage was dysfunctional.